Decentralization in a Unitary State: A Comparative Analysis and Adaptive Governance Design Based on Performance - Panji Hendrarso; Nina Kurnia; Ahmad Subhan; Mutia Rizky Septiani; Gugun Gunawan; Arif Nugroho (Sean Institute, 2025)
Over the past two decades, decentralization has emerged as a primary strategy in governance reform across various countries, including Indonesia. This study aims to evaluate the effectiveness of decentralization within the framework of a unitary state by examining its concepts, implementation models, and impacts on local government performance through a systematic literature review and cross country comparison. By analyzing practices in Indonesia, the Philippines, South Africa, and India, the study finds that the success of decentralization is highly dependent on the alignment between institutional design, fiscal and administrative capacity, and the structure of intergovernmental relations. Indonesia has adopted a controlled asymmetric decentralization model that has succeeded in fostering local innovation but continues to face challenges in coordination and fiscal disparities. The study proposes a new analytical framework that integrates institutional and performance based governance approaches, and emphasizes the importance of fiscal reform, adaptive institutional design, and digital transformation. The main contribution of this study lies in strengthening theoretical discourse and formulating decentralization policy recommendations that are more responsive to local dynamics and future challenges.